Effects of exogenous melatonin on expressional differences of immune-related genes in cashmere goats - Chai, Yuan; Liu, Zaixia; Fu, Shaoyin; Liu, Bin; Guo, Lili; Dai, Lingli; Sun, Yanyong; Zhang, Wenguang; Li, Chun; Liu, Taodi (Frontiers in Genetics, 2022)
The interplay between melatonin and immune system is well recognized in humans. The true integration of research on cashmere goat is still far from clear, especially for cashmere goat maintained in wool and cashmere growth. In this study, we applied various approaches to identify the complex regulated network between the immune-related genes and transcription factors (TFs) and to explore the relationship between melatonin and gene expression in cashmere goats. In total, 1,599 and 1756 immune-related genes were found in the blood and skin of cashmere goats, respectively, and 24 differentially expressed immune-related GO terms were highly expressed in blood after melatonin implantation. We studied the melatonin-dependent networks between the TFs and immune-related genes in cashmere goat. The 3 major regulatory networks were interconnected through TFs. The TFs, such as PHF5A, REXO4, STRAP, JUNB, GATAD2A, ZNF710, and VDR, were also expressed in the blood and skin tissue of cashmere goat. In addition, most genes in these networks, such as VDR, JUNB, and Trib3, were involved in WNT pathway, which is related to cashmere wool growth regulation. On the network basis, we developed a knockout mouse model to identify the network interaction. We observed that 8 high-sulfur protein genes, 12 keratin (KRT) genes, and 19 keratin associated protein (KRTAP) genes related to the growth of cashmere wool were almost not expressed in Trib3−/− rat skin. Our results suggested that the expression of genes related to wool and cashmere growth may be regulated by the interaction network between genes affected by melatonin and immune-related genes. In summary, we outlined some particularly promising ways for future research on immune-related genes of cashmere goats and the role of melatonin in wool and cashmere growth.